PENDIDIKAN ISLAM MULTIKULTURAL DAN DERADIKALISASI DI KALANGAN MAHASISWA - Supardi, Supardi (Universitas Islam Negeri Raden Intan Lampung, 2013)
This study aims to describe the level of multicultural education and deradicalization, and analyze the influence of Islamic education multicultural to de-radicalization of religion. The research was conducted students of teaching primary Faculty Eduacation and Teaching IAIN SMH Banten. The methodology used is quantitative correlation; using a Likert scale questionnaire with five choice. The results show: First, the level multicutural Islamic education and de-radicalization of the religion were high and satisfactory. Secondly there is positive and significant multicultural Islamic education to the deradicalization of religion among the students. The influence of multicultural Islamic education to de- radicalization of religion by 39.69 %. The higher the multicultural education Islamic the higher the de-radicalization of religion. De- radicalization of religion on students can be improved through multicultural islamic education. Therefore the university should implement multiculturalism in all aspects of campus life that de- radicalization religion among students higher.